PELATIHAN VIDEOGRAFI UNTUK PENINGKATAN KAPASITAS SDM UMKM DI DESA GUNUNG PUTRI - Bambang Wardoyo; Moch. Sarif Hasyim; Don Gusti Rao; Adi Masliardi; Doni Mardiyanto; Calvin Pradigta; Tasya Chaerani (Surakarta Abdimas Journal, 2025)
This community service activity was carried out in Gunung Putri Village, Bogor Regency, with the aim of increasing the digital capacity of Micro, Small and Medium Enterprises (MSMEs) through videography training. A total of 25 MSME players participated in the two-day training which included a basic introduction to videography, practice in making promotional videos, and presentation of the participants' work. The training method was conducted in a participatory manner through a combination of theoretical material, technical demonstrations, and hands-on practice. The results of the activity showed that participants were able to produce product promotion videos that were creative, informative, and in accordance with the characteristics of their respective businesses. Documentation of the activity shows the high enthusiasm of the participants, which reflects the need and interest in digital marketing skills. Despite obstacles such as limited tools and limited training time, this activity had a positive impact on improving the digital skills of MSME players, especially in the aspects of branding and promotion. This training is the first step in supporting the digital transformation of local MSMEs to expand market access and improve competitiveness in the digital economy era.